Chemical control of rice whitefly (Aleurocybotus occiduus Maria) in Chitwan, Nepal - Pokhrel, S; Pokhrel, SP (Agronomy Journal of Nepal, 2013)
Effectiveness of five common insecticides was evaluated against a newly established rice insect, Whitefly (Aleurocybotus occiduus Maria) on main season rice (var: Sabitri) at Bharatpur-10, Chitwan (350 m) in 2005. The insecticides tested were: Noorani (Chloropyrifos 50% + Cypermethrin 5% EC) @ 2ml/litre of water, Rogar @ 1.5ml/litre of water, Phoskil (monocrotophos) @ 2ml/litre of water, Furadan @ 1kg a.i/ha and Anumida (Imidacloprid 17.8% SL) @ 1ml/4 litre of water. The plant growth parameters: plant height, number of yellow and green leaves, active and dead tillers and the grain yield were recorded. Anumida (Imidacloprid 17.8% SL) provided perfect control of Whitefly and gave the highest plant height (60 vs 50 cm), highest leaf number (46.7 vs 3.7), highest tillering (4.4 folds), highest green infertile tillers (16.3 vs6.7) with highest number of ears (3.0 vs 0.0) and grain number (26.3 vs 0.0)/hill. Anumida (Imidacloprid 17.8% SL) also provided comparatively lower leaf yellowing and drying (8.5 vs 22.5) then the control. Anumida (Imidacloprid 17.8% SL) @ 1ml/ 4 liter of water is recommended against rice Whitefly however, Rogar @ 1.5 ml/litre of water, Phoskil (monocrotophos) @ 2ml/litre of water, Noorani (Chloropyrifos 50% + Cypermethrine 5% EC) @ 2ml/liter of water and Furadan @ 1kg a.i./ha also can serve the purpose. The hills not using insecticide were completely failure to produce ears and grains. DOI: http://dx.doi.org/10.3126/ajn.v2i0.7520 Agronomy Journal of Nepal (Agron JN) Vol. 2: 2011 pp.42-55